PENGARUH MANAJEMEN ASET DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Kasus pada PT. Tambang Batubara Bukit Asam Tbk. dan PT. United Tractors Tbk.) - Prasetya, Syarief Gerald (STIE Binaniaga, 2011)
Company's goal is to maximize the value of the company. Value of the company is very important for the company because the company maximize the value it will maximize the welfare of shareholders. Efforts that can be done to maximize the value of the company in one of the company through asset management. Asset management companies is an activity which is very important because the management is based on the size of the success of the company during a certain period can be known. Asset management is a potential that is owned by organizations or individuals to achieve the vision, mission and goals, or particular. However, in maximizing the value of a company diisyaratkan a growth company that is a positive development of the company that occurred in a period of timeThe aim of this research is to analyse relevantly of assets management and growth of company, is have influence and relation, or not with value of company. If in research process found by inexistence of relation and influence from assets management and growth of company, so will searching that problem and searching the othe factors perhaps existence relation and influence to value of companiesThe research shows that in PT. Tambang Batubara Bukit Asam Tbk, influential assets management according to significant towards value of companies, that is with level significant as big as 0,012. While in PT. United Tractors Tbk, assets management not influential according to significant towards value of companies, that is with level significant as big as 0,576. In PT. Tambang Batubara Bukit Asam Tbk, influential growth of company according to significant towards value of companies, that is with level significant as big as 0,015. While in PT. United Tractors Tbk, growt of company not influential according to significant towards value of companies, that is with level significant as big as 0,870Result of evaluation in this research is that value of companies do not only be influenced by factor of assets management and growth of company, but there is other factor which can influence such as profitability factor and and efficiency costKey word: management assets, growth of company, value of company